Honeymoon for bees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Pest Control Safe for Bees: a manual and directory for the tropics and subtropics / Adey M., Walker P., Walker P.T. (1986). International Bee Research Association (IBRA) UK, 224 pp.